AI GENERATED CONTENT IN HOSPITALITY MARKETING: IMPACTS ON BRAND IMAGE AND BOOKING INTENTIONS - Saleh, Nur Fathia; Rosli, Nuraina Nadiah (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Artificial intelligence (AI) is reshaping the way hospitality businesses communicate with customers, offering opportunities to deliver personalized, efficient, and engaging marketing messages. While these advancements create new ways to connect with travelers, they also raise concerns about authenticity, trust, and credibility. Customers increasingly question whether AI-generated content truly reflects a brand’s identity or risks appearing impersonal and untrustworthy, issues that are especially critical in hospitality where trust strongly influences booking decisions. This study investigates how AI-generated content affects brand image and booking intentions in the hospitality industry, drawing on two theoretical perspectives: the Technology Acceptance Model (TAM) and the Source Credibility Theory (SCT). TAM explains how customers evaluate technology based on perceived usefulness and ease of use, while SCT highlights the role of trustworthiness and expertise in shaping acceptance of messages. Integrating these theories, the study proposes a framework to understand consumer responses to AI marketing content. Findings from the framework suggest that AI can positively influence brand perception and drive bookings, but only when messages are seen as credible, authentic, and aligned with customer expectations. Theoretically, this research extends TAM and SCT by applying them to AI-driven hospitality marketing. Practically, it provides guidance for marketers on crafting AI-generated messages that foster trust and credibility while avoiding the risks of over-automation. By addressing current concerns about authenticity and transparency, this study fills a key gap in understanding AI’s role in hospitality marketing and lays the foundation for future empirical research in real-world contexts.